The Role Of Bilateral Agreement As Pillars Post-Pandemic Economic Resilience: Capabilities Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) To Trade Growth Accelerator In Indonesia - Nabila Yasmin Namira (Mediasi: Journal of International Relations, 2021)
The Covid-19 pandemic hit the world in 2020, causing various changes that greatly affected globalstability, which once the economic sector. The Indonesian economy has not spared from the effectsof the pandemic that has arisen from various social restrictions, resulting in a quite drastic economicdecline. The Indonesian government are optimizing economic cooperation with several partnercountries to recover the post-pandemic economy. The Indonesia-Australia ComprehensiveEconomic Partnership Agreement (IA-CEPA) are comprehensive economic partnership betweenIndonesia and Australia. The IA-CEPA provides many conveniences that Indonesia can utilize torecover the economy after the Covid-19 pandemic. The Economic Powerhouse Strategy arecollaboration of excellence carried out by Australia and Indonesia to create higher-quality products.In addition, the IA-CEPA collaboration also provides easy access by eliminating tariffs so thatproducts from Indonesia can compete at lower prices. This study purpose to determine the role ofthe IA-CEPA in Indonesia's trade growth after the Covid-19 pandemic. Through descriptivequalitative methods, it can be concluded that the IA-CEPA has played the role as an accelerator ofIndonesian trade through the Economic Powerhouse strategy. That Australia are supplier of rawmaterials, and Indonesia acts as the center for processing and marketing in the global market.Another advantage are the elimination of entry tariffs for products from Indonesia to the Australianmarket. So that the Indonesian economy has returned to stability after the Covid-19 pandemicthrough international trade activities supported by the IA-CEPA. This research based onIslamization Concept, namely, Ta’awun in Islam, which contains Islamic values.